2020
DOI: 10.1039/d0an00778a
|View full text |Cite
|
Sign up to set email alerts
|

A computational and experimental study of the fragmentation of l-leucine, l-isoleucine and l-allo-isoleucine under collision-induced dissociation tandem mass spectrometry

Abstract: The isomeric amino acids leucine, isoleucine and L-allo-isoleucine, are essential to many vital biological processes and are therefore of interest to the fields of metabolomics and proteomics. Their discrimination can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…From the product ion observed at m / z 142.1 and discussed in the previous section, the ions [PCP­(A) – C 3 H 8 O 2 NP] + observed at m / z 140.1 and [PCP­(A) – C 3 H 6 O 2 NP – HCl] + observed at m / z 106.1 may be obtained by the elimination of H 2 and HCl as shown in Figure A,B, respectively. The elimination of H 2 from amino acids and nucleobases in CID experiments employing positive mode ESI has been previously reported in the literature. Such secondary reactions are experimentally viable in our work due to the high collision pressures employed in the CID conditions, which does not preclude multiple collision scenarios.…”
Section: Resultsmentioning
confidence: 56%
“…From the product ion observed at m / z 142.1 and discussed in the previous section, the ions [PCP­(A) – C 3 H 8 O 2 NP] + observed at m / z 140.1 and [PCP­(A) – C 3 H 6 O 2 NP – HCl] + observed at m / z 106.1 may be obtained by the elimination of H 2 and HCl as shown in Figure A,B, respectively. The elimination of H 2 from amino acids and nucleobases in CID experiments employing positive mode ESI has been previously reported in the literature. Such secondary reactions are experimentally viable in our work due to the high collision pressures employed in the CID conditions, which does not preclude multiple collision scenarios.…”
Section: Resultsmentioning
confidence: 56%
“…However, comprehensive studies investigating PQ's antimicrobial chemicals are still scarce, and the NMR chemical identification usually required milligrams of pure compound, which is time-consuming to purify. In recent years, the advanced Orbitrap Elite Hybrid Mass Spectrometer, which combines a novel high-field orbitrap mass analyzer with a premier dual-pressure linear ion trap mass spectrometer, greatly improved MS and MS n performance and versatility, and it has become a reliable technique for a targeted and a non-targeted analysis of the chemical structure, requiring only picogram of the sample (Denisov et al, 2012;Jiang et al, 2020;Zhao et al, 2020). LC-HRMS/MS (high-resolution mass spectrometry) and MS n provide retention time, extract m/z and its fragmentation, from which the structure normally can be inferred based on comparison with standards, or published spectra of compound databases, MS/MS libraries, and molecular networking (Allen et al, 2014;Schymanski et al, 2014;Fisher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Different protein and non-protein amino acids were unequivocally identified by comparing their retention time and MS/MS fragmentation pattern with those obtained for commercial standards. ), and 44 (C 2 H 6 N + ) (Jiang et al, 2020) which were also found in Leucine commercial standard. The content of pyroglutamic acid in all the alkalization degrees studied was similar and lower than that obtained in CN, but a clear trend with the alkalization degree was not observed.…”
Section: Tablementioning
confidence: 56%